(untitled) (Swiss Medical Weekly, 2021)
OBJECTIVES Characteristics of Swiss patients with systemic sclerosis have not been described so far. The aim of the current study was to identify unmet needs in comparison with other European countries that could inform specific interventions to improve the care of systemic sclerosis patients. METHODS We analysed Swiss and other European systemic sclerosis patients registered in European Scleroderma Trials And Research (EUSTAR) and the Very Early Diagnosis Of Systemic Sclerosis (VEDOSS) cohort. Demographics, clinical profiles, organ involvement and survival of established, early/mild and very early / very mild systemic sclerosis patients were described and compared between the cohorts. RESULTS We included 679 Swiss and 8793 European systemic sclerosis patients in the analysis. Over 95% of patients in both cohorts were Caucasian, disease subsets were similar, and no age difference was found. The Swiss cohort had more male patients (25% vs 16% European, p = 0.005) and higher prevalence of early/mild and very early / very mild patients (26.1 vs 8.5% European and 14.9% vs 6.7% European, respectively, both p <0.0001). Disease duration in established systemic sclerosis patients at first presentation was numerically shorter but not significant in the Swiss cohort: 5.0 years (1–12) Swiss vs 6.0 years (2–12) years European, p = 0.055). Despite the earlier referral of Swiss patients to systemic sclerosis expert centres, they showed evidence of more severe disease, particularly in the limited cutaneous systemic sclerosis subset, but no differences in overall survival on longitudinal follow-up were observed. CONCLUSION This is the first report of the national Swiss EUSTAR cohort. It identifies earlier referral to systemic sclerosis expert centres, before major organ damage occurs, and when outcome can still be modified, as a priority to improve care of patients with systemic sclerosis.